Engineering foot-and-mouth disease virus serotype O IND R2/1975 for one-step purification by immobilized metal affinity chromatography. Issue 5 (September 2015) - Biswal, Jitendra K.; Bisht, Punam; Subramaniam, Saravanan; Ranjan, Rajeev; Sharma, Gaurav K.; Pattnaik, Bramhadev
Abstract Immobilized metal affinity chromatography (IMAC) allows for the efficient protein purification via metal affinity tag such as hexa-histidine (His6) sequence. To develop a new chromatography strategy for the purification and concentration of foot-and-mouth disease virus (FMDV) particles, we inserted the His6-tag at the earlier reported site in the VP1 G-H loop of the FMD virus serotype O vaccine strain IND R2/1975. Display of the His6-tag on the capsid surface, endowed the virus with an increased affinity for immobilized nickel ions. We demonstrated that the His6-tagged FMDV could be produced to high titre and purified from the infected BHK-21 cell lysates by IMAC efficiently. Further, a 1150-fold reduction in protein contaminant level and an 8400-fold reduction in DNA contaminant level were achieved in the IMAC purification of His6-tagged FMDV. Through various functional assays it has been found that the tagged virus retains its functionality and infectivity similar to the non-tagged virus. The affinity purification of the His6-tagged FMDV may offer a feasible, alternative approach to the current methods of FMDV antigen purification, concentration and process scalability.